Structures under shock and impact II proceedings of the second international conference, held in Portsmouth, U.K., 16th-18th June, 1992 - Bulson, P. S., 1925- (Thomas Telford, 1992)
Terrorist attacks on buildings, bridges and transport vehicles mean that more attention must be given at the design stage to the effects of explosions and impact, and to high speed penetration of attack weapons. This book brings together the experience of scientists in the behaviour of concrete and metal structures to blast, penetration and collision.